Avaliação de Interações entre Professor e Alunos na Educação Matemática: ensino e aprendizagem de recursos pedagógicos - Lopes Júnior, Jair [UNESP]; Peralta Sparvoli, Deise Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), Departamento de Matemática, 2009)
The aim of this paper is to discuss the teachers' need, as autonomous professionals, to evaluate their own pratice. Considering that Descriptive Functional Analysis (DFA) may be a pedagogical method for analysis, implementation, and change of teachers' mathematics teaching practices, the objective of the present research was to teach repertoires compatible with DFA to two mathematics teachers in elementary schools of São Paulo state. When teachers are responsible for evaluation and self evaluation, they recognize themselves as fundamental agents of transformation in education.
Evaluation of Teacher-student Interactions in Mathematics Education: the teaching and the learning of pedagogical resources.
Keywords: Mathematics Education; Descriptive Functional Analysis; Pedagogical Resources